CARDIAC STRAIN MRI: PRINCIPLE, TECHNIQUE AND CLINICAL APPLICATIONS - Nguyễn , Ngọc Tráng; Nguyễn , Thị Huyền (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Cardiac strain MRI is an advanced imaging technique that quantifies myocardial deformation, providing comprehensive insights into cardiac function. The principle behind this method is based on tracking the motion of tissue features. Clinically, cardiac strain MRI is used to detect early signs of myocardial dysfunction and management in various conditions such as ischemic heart disease, cardiomyopathies, chemotherapy-induced cardiotoxicity,… With its ability to provide precise and detailed information about the myocardium, cardiac strain MRI is becoming an essential tool in cardiovascular diagnostics and research.